Landscapes of Care Immigration and Health in Rural America - Sangaramoorthy, Thurka (Studies in Social Medicine, 2023)
This insightful work on rural health in the United States examines the ways immigrants, mainly from Latin America and the Caribbean, navigate the health care system in the United States. Since 1990, immigration to the United States has risen sharply, and rural areas have seen the highest increases. Thurka Sangaramoorthy reveals that that the corporatization of health care delivery and immigration policies are deeply connected in rural America. Drawing from fieldwork that centers on Maryland's sparsely populated Eastern Shore, Sangaramoorthy shows how longstanding issues of precarity among rural health systems along with the exclusionary logics of immigration have mutually fashioned a "landscape of care" in which shared conditions of physical suffering and emotional anxiety among immigrants and rural residents generate powerful forms of regional vitality and social inclusion. Sangaramoorthy connects the Eastern Shore and its immigrant populations to many other places around the world that are struggling with the challenges of global migration, rural precarity, and health governance. Her extensive ethnographic and policy research shows the personal stories behind health inequity data and helps to give readers a human entry point into the enormous challenges of immigration and rural health.